Participation in Social Skills Therapy is Associated With Enhanced Recall Memory by Children With Down Syndrome: An Exploratory Study. Issue 4 (July 2020) - Milojevich, Helen M.; Slonecker, Emily M.; Lukowski, Angela F.
Participation in social skills therapy (SST) facilitates cognitive functioning in children with developmental disabilities. The present pilot study examined whether participation in SST was associated with enhanced encoding and 1-month delayed recall in children with Down syndrome (DS). Children were presented with novel three-step event sequences in an elicited imitation procedure. Immediate imitation was permitted as an index of encoding; long-term memory was assessed 1 month later. Parents completed questionnaires inquiring about children's participation in SST. Participation in SST was associated with enhanced encoding of temporal order information and 1-month delayed recall of individual target actions. In addition, encoding mediated the relation between group and 1-month delayed recall. The conducted research indicates that involvement in SST may be beneficial for children with DS despite their noted strengths in imitation and social learning. As such, additional experimental work is warranted to determine causality.